Recent advances in mitochondria-targeted porphyrin-based metal-organic frameworks for enhanced cancer therapy - Tao, Jiawen; Yuan, Zhifei; Zhou, Mengjiao (Frontiers in Pharmacology, 2026)
Porphyrin-based metal-organic frameworks (MOFs) offer exceptional advantages for cancer therapy, including high photosensitizer loading, tunable nanostructures, and suppression of porphyrin self-quenching. By functionalizing with mitochondria targeting ligands, these platforms deliver reactive oxygen species (ROS) precisely to mitochondria, the oxygen-rich and ROS-sensitive organelle, dramatically enhancing photodynamic therapy (PDT) efficacy. This design paradigm has been successfully extended to sonodynamic therapy (SDT) and radiotherapy/radiodynamic therapy (RT-RDT), where porphyrin-MOFs integrate additional functions such as glutathione depletion, CO/H2S gas release, or immune activation. Upon ultrasound or X-ray irradiation, these systems synergistically amplify mitochondrial oxidative damage, overcoming hypoxia, antioxidant defenses, and apoptosis resistance. The diversified applications (PDT, SDT and RDT) exemplifies a multimodal strategy that leverages the unique physicochemical properties of porphyrin-MOFs to achieve spatiotemporally controlled, organelle-specific therapy. Looking ahead, the development of intelligent, stimuli-responsive porphyrin-MOF nanoplatforms holds great promise for clinical translation, enabling integrated theranostics and personalized cancer treatment through precise mitochondrial targeting.